Fiscal Policies in the European Union during the Crisis - Ferreiro, Jesús; Gálvez, Catalina; González, Ana (Panoeconomicus, 2015)
The paper studies the fiscal policies implemented in the European Union countries since the beginning of the current crisis. With this aim in mind we have analyzed separately the expansionary fiscal policies implemented at the first stage of the crisis and the fiscal consolidation policies that became widespread at the beginning of the current decade. Studying the content of the national fiscal policies (discretionary measures versus built-in stabilizers, revenue-based versus expenditure-based fiscal policies, the relationship existing between the size of the fiscal impulses-adjustments and the composition of these measures) shows the significant differences between the fiscal policies implemented in the European Union countries.Key words: European Union, Fiscal policy, Economic crisis.JEL: E62, E65, H62, O52.